The complete mitogenomes of all four Cryptospiza species (Aves: Estrildidae) - J. Dylan Maddox; Erica Zahnle; Kit McDonnell; Felix Grewe; Thomas P. Gnoske; John M. Bates; Shannon J. Hackett (Mitochondrial DNA. Part B. Resources)
Crimsonwings are estrildid finches found in the understory of montane rainforests of sub-Saharan Africa. The genus includes four species: Cryptospiza jacksoni Sharpe 1902, C. shelleyi Sharpe 1902, C. reichenovii (Hartlaub 1874), and C. salvadorii Reichenow 1892. The first two are endemic to the Albertine Rift, while the latter two are more widespread. Despite being well-represented in museum collections, genetic resources are scarce. Here we provide complete mitogenomes for all four species, each containing the standard 37 avian genes. Analyses showed C. shelleyi as sister to the other three species, with C. reichenovii and C. salvadorii being highly similar (99.2%). Further research is needed to explore their evolutionary history.